2012
DOI: 10.1096/fj.12-209080
|View full text |Cite
|
Sign up to set email alerts
|

Functional segregation and emerging role of cilia‐related cytosolic carboxypeptidases (CCPs)

Abstract: Recent experimental data indicating axonal regeneration, axogenesis, dendritogenesis, and ciliary axoneme assembly and wellness have linked the role of cytosolic metallocarboxypeptidase 1 (CCP1/AGTPBP1/Nna1) to the microtubule network. In addition, 5 of the 6 mammalian ccp genes have been shown to participate in post-translational modifications of tubulin, which occur in the microtubules of neurons, mitotic spindles, cilia, and basal bodies. Here, we compile evidence for the idea that the occurrence of CCPs st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Examples of hyperglutamylation leading to disease include mutations in the deglutamylase AGBL5, associated with retinal degeneration in humans [54], and loss of the deglutamylase Ccp1, which causes progressive neurodegeneration and sperm immotility in mice [20]. A growing list of reports links hypoglutamylation to disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of hyperglutamylation leading to disease include mutations in the deglutamylase AGBL5, associated with retinal degeneration in humans [54], and loss of the deglutamylase Ccp1, which causes progressive neurodegeneration and sperm immotility in mice [20]. A growing list of reports links hypoglutamylation to disease.…”
Section: Discussionmentioning
confidence: 99%
“…Joubert syndrome [17], blindness [18], and schizophrenia [19], are associated with defects in TTLL glutamylases. Defects in the Ccp1 deglutamylase cause neuronal degeneration in mice [20]. How dysregulated glutamylation might contribute to human disease is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that CCP2 plays a more important role in the adult. Recently, it has been shown in HeLa cells that CCP2 colocalizes with ␥-tubulin within centrioles and with polyglutamylated tubulin within the basal bodies of primary cilia (34). One study suggested that CCP2 functions as a tubulin tyrosine carboxypeptidase (24).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that loss of CCPP-6 gene function resulted in increased polyglutamylation, whereas overexpression resulted in decreased polyglutamylation. In cultured HeLa cells, CCP6 has been found to colocalize with centrioles and basal bodies (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation